Utility of Contrast-Enhanced Computed Tomography for Differentiating Pancreatic Ductal Adenocarcinoma from Inflammatory Mass in Chronic Calcific Pancreatitis - Pratap, Thara; Jacob, Dhanya; Venkatesh, Sudhakar K.; Jalal, Muhammed Jasim Abdul; K., Vishnu (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Objective The aim of this study was to identify the most useful contrast-enhanced computed tomography (CECT) features for differentiating pancreatic ductal adenocarcinoma (PDAC) from mass-forming chronic pancreatitis (MFCP) in chronic calcific pancreatitis (CCP).Methods In total, 101 patients with CCP and focal pancreatic mass formed the study group. Sixteen qualitative and four quantitative parameters were analyzed. Qualitative parameters included size, site, margin, intralesional hypodensity, collateral duct sign, abrupt pancreatic duct (PD) cutoff, upstream PD dilatation, distal pancreatic atrophy, double duct sign, enhancement pattern, contrast attenuation, peripancreatic inflammation, vascular involvement, regional nodes, and metastasis. Quantitative parameters included duct-to-body ratio, common bile duct (CBD) diameter, main pancreatic duct (MPD) diameter, and carcinoembryonic antigen 19-9 (CA19-9). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated for prediction of PDAC. A receiver operating characteristic (ROC) curve analysis was performed and the area under ROC curve (AUROC) was calculated to determine diagnostic accuracy to assess the optimal cutoff.Results PDAC was confirmed in 48 patients and MFCP in 53 patients. A duct-to-body ratio greater than 0.48 had 95.5% sensitivity, 83.3% specificity, 80.8% PPV, 96.2% NPV, and 88.5% accuracy for predicting PDAC. A CBD diameter cutoff ≥9.5 mm had an accuracy of 75% (p < 0.019) and an MPD cutoff ≥6.25 mm had an accuracy of 67.8% (p = 0.008) for predicting PDAC. On binary logistic regression, the duct-to-body ratio was found to be the significant independent factor associated with malignancy.Conclusion A duct-to-body ratio greater than 0.48, intralesional hypodensity, and abrupt duct cutoff are the most helpful computed tomography (CT) features for distinguishing PDAC from MFCP in CCP. On binary logistic regression, the duct-to-body ratio was found to be a significant independent factor. Interspersed normal parenchyma was observed as a very specific sign of MFCP. Intraparenchymal hypodensity has high specificity, but further validation is needed.
Keywords: pancreatic ductal carcinoma; inflammatory mass; chronic pancreatitis; pancreatic calcification